Cyclic GMP mimics the muscarinic response in Xenopus oocytes: identity of ionic mechanisms. - Dascal, N (1982)
Acetylcholine (AcCho) elicits four distinct membrane responses in Xenopus oocytes; the responses can be studied by using the voltage clamp technique. The fastest of the responses, a transient inward current (D1 response), is muscarinic, being evoked by oxotremorine and blocked by atropine but not by curare or hexamethonium. The action of AcCho is cooperative, three transmitter-receptor complexes being required to cause a membrane conductance change, and the dose-response curve in most cases can be fitted by an equation assuming the existence of two binding sites with an affinity ratio of about 11. Guanosine 3',5'-cyclic monophosphate and the 8-bromo and dibutyryl derivatives cause a response similar to D1 in both its time course and the underlying ionic mechanism. The nucleotide-generated response has a smaller amplitude than the AcCho-generated D1.